PENGARUH PENJUALAN, BEBAN POKOK PENJUALAN, DAN PAJAK PENGHASILAN TERHADAP LABA BERSIH (STUDI KASUS PERUSAHAAN DI BEI SEKTOR INDUSTRI MAKANAN DAN MINUMAN PERIODE 2014 – 2019) - Eko Purwanto (LPPM UNIBI, 2021)
This study intends to examine the effect of sales, cost of goods sold, and income tax on company net income. Sales refer to income from the main results of the company's operations, cost of goods sold are all costs related to production and others for making a certain product at a certain amount, while income tax is a company's obligation to the state which is binding. The population in this study were all food and drink industry sector companies listed on the Indonesia Stock Exchange from 2014 to 2019. The sample selection was using a non-probability method with certain criteria in order to obtain 12 companies and 72 financial reports. The regression model is used in data analysis, it is found that sales results and cost of goods sold have no effect on net income, while taxes have an effect on company net income.